GWT: cool & useful stuff - Geary, David (Prentice Hall, 2007)
"This session shows you how to flat out kick ass with GWT. You'll see how to create custom widgets, from low-level to high-level, and in between. You'll see how to implement: drag and drop; simple windows that pop up in the browser's client area; viewports that smoothly drag their views in reaction to user input; and tables with columns that you can dynamically resize. Along the way, we'll explore some of the more advanced aspects of GWT, such as: telling the browser to butt out of event handling; using timers for iPhone-like animations; capturing events to increase performance; and how you can directly create and manipulate a widget's DOM element. If you're looking to learn some advanced GWT techniques and add some more sizzle to your web applications, don't miss this nonstop barrage of code and killer demos."--Resource description page